A gíria de grupo entre "meninas" do sistema socioeducativo a partir do cronotopo e do lugar de fala. - Sandes, Marlene Barros (2023)
This research brings an overview of the institutionalization of adolescent women in the deprivation and restriction of freedom of the socio-educational system from the constitution of language, with slang being the focus used. We start from the dialogic, sociohistorical and ideological perspective of language advocated by Bakhtin (2003; 2006; 2010; 2013; 2014). For this thinker and his Circle, language has a dialogical, experiential and ideological character and, in this sense, adolescents in internment and semi-liberty constitute themselves as subjects in the self-other relationship in the discursive time-space (chronotope) of which constitutes the socio educational measure and from the place of speech. Given the pandemic situation and the protocols and procedures for suspending research in the spaces of deprivation and restriction of liberty, we built the investigation under a qualitative approach, the methodology being based on documentary analysis and bibliographic survey. Based on a brief analysis of the gender category and on the foundations of Sociolinguistics (PRETI, 1983; 1984; 2000; 2004; 2007) we consider that group slang reveals the spoken language, described, observed, analyzed in its social context and in use situations. The analyzes point out that, in addition to possible aspects of limitations of this linguistic repertoire, the stigmatization of the subjects who use it and the subversive character that is peculiar to it, slang involves processes that combine identification, belonging, constituting the group identity between deprived adolescents and adolescents restricted freedom. Among other approaches punctuated throughout the text, we propose to answer in this investigation the following questions: How is gender policy in socio-educational? What paths do adolescents take to confirm the alterities present in the verbal codes created or reproduced from the gender category? Why is the use of group slang as a symbolic and discursive language so used by adolescents in internment and semi-liberty? What relationships are built between the subject, the place of speech, the group slang and the chronotopes of the socio-educational measure in a closed environment? To address notes on the place of speech, we start from the webs that are built between Anthropology and Philosophy, questioning conceptions that involve women in their social and historical construction under the threshold of the studies punctuated by Ribeiro (2016; 2017). All these issues contribute to the understanding of the adolescent in a socio-educational measure in a closed environment and the discursive and/or interactive relationships that she establishes through slang, a group sign that, among other aspects, identifies, inscribes and constitutes them as subjects in the processes that constitute institutionalization.